Risk Analysis regarding the costs of a residential civil works project via Python - Santos, José Antônio Lima (2022)
It is essential to analyze the projects risks that you want to execute, especially in the construction sector, cause they are highly regarded as external conditions such as: climatic, political and public health issues. Most designers use a magnification factor to define the maximum cost, however, it can be considered an overpassed way. To innovate the risk analysis in Civil Construction, the present work carried out two simulations via computational Monte Carlo Method in the Python Programming Language. The first simulation was made using the Risk Oriented Identification Approach Method and the Precedence Diagram Method and PERT/CPM Tool. Based on the above considerations, the main goal is to present a comparison between two risk analysis methodologies to later help civil construction entrepreneurs to better assess the budgetary risks of their projects. Through the results obtained by the computer simulation process were possible the identification of possible costs, and from then on, planning the best project planning.